Two-dimensional amine and hydroxy functionalized fused aromatic covalent organic framework - Mahmood, Javeed; Ahmad, Ishfaq; Jung, Minbok; Seo, Jeong-Min; Yu, Soo-Young; Noh, Hyuk-Jun; Kim, Young Hyun; Shin, Hyung-Joon; Baek, Jong-Beom (Communications chemistry, 2020)
Ordered two-dimensional covalent organic frameworks (COFs) have generally been synthesized using reversible reactions. It has been difficult to synthesize a similar degree of ordered COFs using irreversible reactions. Developing COFs with a fused aromatic ring system via an irreversible reaction is highly desirable but has remained a significant challenge. Here we demonstrate a COF that can be synthesized from organic building blocks via irreversible condensation (aromatization). The as-synthesized robust fused aromatic COF (F-COF) exhibits high crystallinity. Its lattice structure is characterized by scanning tunneling microscopy and X-ray diffraction pattern. Because of its fused aromatic ring system, the F-COF structure possesses high physiochemical stability, due to the absence of hydrolysable weak covalent bonds. Two-dimensional covalent organic frameworks (2D COFs) are commonly synthesised through dynamic covalent chemistry, as it allows for thermodynamic ‘error correction' which enhances crystallinity. Here a crystalline 2D COF with amine and hydroxyl functional groups within the pores is synthesised through kinetically-controlled reactions.